Consciência e adequação linguísticas: uma proposta didática com o poema-slam - Santos, Cinthia Pires dos (2023)
The present research developed within the scope of the Postgraduate Professional Master's Program in Letters at the Federal University of Uberlândia – PROFLETRAS-UFU – had as its main objective, the elaboration and application of a didactic proposal that could provide opportunities for the development of research in the classroom. class with a view to contributing to the development of awareness about the heterogeneity of the language, on the part of students of the 9th year of Elementary School of a municipal school, in São Simão-GO. To this end, we opted for didactic work with the slam-poem because we believe that this genre is quite suitable for the development of the notion of linguistic adequacy. For this, we will base ourselves on the contributions of Educational Sociolinguistics to the teaching of Portuguese (BORTONI-RICARDO, 2004; 2005; BAGNO, 2013; FARACO, 2008; FARACO; ZILLES, 2015, among others). With regard to the conception of gender, we used Bakhtin's (2000) contributions as a theoretical framework; however, we also brought to our research, the contributions of Marcuschi (2006) regarding the definition of mixed genre, bearing in mind that in the light of this author's reflections, we classified the slam-poem as a mixed genre. For the elaboration of the didactic proposal, workshops were conceived (ARRIADA; VALE, 2012) that provided the development of linguistic research in the classroom, also collaborating for the development of scientific literacy (SILVA, 2018; CUNHA, 2017; SASSERON; CARVALHO, 2011) of students, in addition to providing youth protagonism in the classroom (STAMATO, 2008). The methodology adopted was Thiollent's action-research (1996) and as a final product, we present an activity notebook for students of the Final Series of Elementary School, in tune with the National Common Curricular Base (BRASIL, 2018), in order to promote the awareness about the heterogeneity of language, as well as the need for linguistic adaptation to the most diverse social practices of language.